2020
DOI: 10.1186/s12876-019-1154-2
|View full text |Cite
|
Sign up to set email alerts
|

The challenging diagnosis and treatment of duodenal diverticulum perforation: a report of two cases

Abstract: Background: The duodenum is a common site for diverticulum formation. Most of the duodenal diverticula are asymptomatic, incidental findings. Perforation is a rare but potentially lethal complication of duodenal diverticular disease. Surgery remains the mainstay of treatment for perforated duodenal diverticula. In recent years, a few cases were successfully managed either conservatively or with endoscopy. Case presentation: We present two cases of female patients treated in our department for duodenal divertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Based on our search on PubMed (2013-present), there have been 29 reports of non-traumatic, noniatrogenic DDP (Table 1) [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Including our case, the location of DDP was at D2 in 20 cases (67%) and D3 in six cases (20%).…”
Section: Discussionmentioning
confidence: 83%
“…Based on our search on PubMed (2013-present), there have been 29 reports of non-traumatic, noniatrogenic DDP (Table 1) [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Including our case, the location of DDP was at D2 in 20 cases (67%) and D3 in six cases (20%).…”
Section: Discussionmentioning
confidence: 83%
“…4 ). Duodenal diverticulum is commonly an incidental diagnosis demonstrated during ERCP, and its presence in the duodenum is similarly associated with bleeding, infection, biliary obstruction and perforation [ 8 , 9 ]. The adjacent diverticulum may interfere with the normal emptying mechanism of the ductal systems, predisposing patients to biliary obstruction and stent migration.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may complain of back pain, especially if the perforation is retroperitoneal. Other symptoms will be fever, nausea, and vomiting [15]. CT is effective for the diagnosis showing extraluminal gas and extraluminal fluid, and it is the most useful modality in the diagnosis of a perforated duodenal diverticulum [15].…”
Section: Discussionmentioning
confidence: 99%
“…Eeckhout et al reported the endoscopic approach to the abdominal abscess due to a perforated duodenal diverticulum [8]. To date, there are only few reports of endoscopic treatment selected for perforated duodenal diverticula [15].…”
Section: Discussionmentioning
confidence: 99%